Dampak Brand Ambassador Tanpa Relevansi pada Produk terhadap Brand Image Perusahaan Smartphone - Muhammad Aqshel Revinzky Nizar (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This research aims to determine the influence of Brand Ambassadors on the Brand Image of Smartphone companies. Brand Ambassador measurement in this research uses four dimensions, namely Visibility, Attraction, Credibility, and Power. Meanwhile, Brand Image uses three dimensions, namely Strength of Brand Association, Advantage of Association, and Uniqueness of Brand Association. The research method used is a survey with simple regression analysis. The sample taken was 100 respondents who were generation Z born in the period 1995-2011 who live in the city of Bandung and know or have heard of smartphone companies and have also heard or seen Brand Ambassadors in advertisements on television and social media held by the company. The sampling technique is Purposive Sampling. The results of data processing from the questionnaire show a good assessment of the Brand Ambassador and also the Brand Image of the Smartphone company. The value of 0.471 from the correlation analysis shows that there is a medium level relationship between the Brand Ambassador and the Brand Image